Diversity of soils, vegetation and biotopes of the regional landscape park “Balka Kobylna” - Krasova, Olha; Dolyna, Oleksandr; Smetana, Oleksiy; Lysohor, Liudmyla (ScienceRise: Biological Science, 2020)
The article considers the patterns of spatial organization of vegetation and soil cover and the biotopic diversity of the regional landscape park, the territory of which has recently become part of the Emerald Network. The aim of the study is to find out the current state of the diversity of soils, plant communities and biotopes of the territory of the regional landscape park “Balka Kobylna”. Materials and methods. When conducting the geobotanical work, generally accepted methods were used. The soil diagnostics was carried out using soil genetic, morphological and laboratory experimental methods. Biotopes are identified in accordance with the developments, presented in the National Habitat Catalogue of Ukraine; the lower levels of the biotopic hierarchy correspond to the syntaxa of the latest “Prodrome of the vegetation of Ukraine”. Results. The composition of the typological units of the soil cover and the features of their spatial differentiation were ascertained, the diversity of plant communities was evaluated, and the patterns of the mutual arrangement of soil and plant territorial units were revealed. It was shown, that the communities of the true steppes are confined to southern chernozems with different degrees of development; on sod-steppe soils, the vegetation of the true steppes is replaced by petrophytogenic one. A classification scheme of biotopes of the territory of the RLP was compiled, represented by six types of the highest classification units; lower levels of the biotopic hierarchy represent the syntaxonomical division of vegetation. Conclusions. As a result of studying the soil cover of RLP “Balka Kobylna”, 23 soil varieties, included in eight soil types, were identified. 30 formations and 8 cenostructures of communities with the dominance of a certain species that did not receive the status of formations in the dominant classification were identified. In addition to the six natural types, we noted some synanthropic phytocoenoses in RLP. The typological scheme of biotopes of RLP “Balka Kobylna”, compiled on the basis of the “National Habitat Catalogue of Ukraine”, includes 6 types of the highest hierarchical level, 8 units of biotopes of the second level, 11 – of the third one, 6 – of the fourth one (including three more subtypes). The results of the studies indicate the high sozological value of the investigated territory and are the basis for the management activity on the lands of the protected object and the development of measures for the biodiversity restoration